C3 POLYMORPHISM IN HYPERLIPOPROTEINEMIA (HLP) - D.D. FARHUD (Tehran University of Medical Sciences, 1989)
C3 typing was performed, by agarose gel electrophorisis, in 147 German patients suffering from hyperlipoproteinemia. The control group consisted of 322 healthy Germans. High frequencies of non-typeable sera, varying between 16.66 and 35.71% in different HLP types, found in the present investigation are notable and are a clue for chemical denaturation of C3 protein in HLP patients. Statistical analysis showed significant results (P.0.001) in all five HLP types, as well as in the total, in comparison with the control group.